2019
DOI: 10.3390/nu11071591
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Food Systems: Significance and Emerging Strategies Towards Improved Viability and Delivery of Enhanced Beneficial Value

Abstract: Preserving the efficacy of probiotic bacteria exhibits paramount challenges that need to be addressed during the development of functional food products. Several factors have been claimed to be responsible for reducing the viability of probiotics including matrix acidity, level of oxygen in products, presence of other lactic acid bacteria, and sensitivity to metabolites produced by other competing bacteria. Several approaches are undertaken to improve and sustain microbial cell viability, like strain selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
387
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 534 publications
(407 citation statements)
references
References 262 publications
6
387
0
14
Order By: Relevance
“…It was found by Praepanitchai et al () that survival of L. plantarum was detected in simulated digestive conditions when coated with alginate coating. Terpou et al () predicted that microencapsulation improves the viability of probiotics in different carrier foods. Similar results were previously reported by (Azarkhavarani, Ziaee, & Hosseini, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found by Praepanitchai et al () that survival of L. plantarum was detected in simulated digestive conditions when coated with alginate coating. Terpou et al () predicted that microencapsulation improves the viability of probiotics in different carrier foods. Similar results were previously reported by (Azarkhavarani, Ziaee, & Hosseini, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study conducted by Pavli et al , , sodium alginate films were found to be effective in delivering the probiotic on the sliced ham. In an earlier study, kappa‐carrageenan/locust bean gum and sodium alginate were found as the most promising performing system for L. rhamnossus GG survivability (Terpou et al , ). The above‐said properties prompted to use a pectin–alginate–casein composite for the incorporation of probiotic in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to entrapping materials, polysaccharides (alginate, plant/microbial gums, chitosan, starch, k-carrageenan, cellulose acetate phthalate), as well as proteins (gelatin, milk proteins) and fats are proposed, but the use of gum or biopolymeric matrices is preferred [58][59][60][61]. Good reviews about probiotic microencapsulation can be found in the papers of Mitropoulou et al [62], De Prisco and Mauriello [63], and Terpou et al [64]. Apart from the kind of material, the performances of probiotic entrapment could be successfully improved through the use of some coadjutants and/or protectants [65][66][67].…”
Section: Encapsulationmentioning
confidence: 99%